2017
DOI: 10.1242/bio.030817
|View full text |Cite
|
Sign up to set email alerts
|

NGF reprograms metastatic melanoma to a bipotent glial-melanocyte neural crest-like precursor

Abstract: Melanoma pathogenesis from normal neural crest-derived melanocytes is often fatal due to aggressive cell invasion throughout the body. The identification of signals that reprogram de-differentiated, metastatic melanoma cells to a less aggressive and stable phenotype would provide a novel strategy to limit disease progression. In this study, we identify and test the function of developmental signals within the chick embryonic neural crest microenvironment to reprogram and sustain the transition of human metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The relationship between embryogenesis and metastasis is enticingly supported by studies by Illmensee and Mintz (54) and Kulesa and colleagues (55), who injected metastatic melanoma cells into embryos and found that the tumor cells differentiated into normal, nontumorigenic tissues. Kasemeier-Kulesa and colleagues subsequently showed that for specific cells, responses to neural growth factor resulted in bipotent precursor cells (56).…”
Section: Developing a Metastatic Cellmentioning
confidence: 99%
“…The relationship between embryogenesis and metastasis is enticingly supported by studies by Illmensee and Mintz (54) and Kulesa and colleagues (55), who injected metastatic melanoma cells into embryos and found that the tumor cells differentiated into normal, nontumorigenic tissues. Kasemeier-Kulesa and colleagues subsequently showed that for specific cells, responses to neural growth factor resulted in bipotent precursor cells (56).…”
Section: Developing a Metastatic Cellmentioning
confidence: 99%
“…Issues can arise as GM-CSF is used as an adjuvant in some melanoma treatments, and the GM-CSF secreting tumors can get an accelerated progression ( Aliper et al , 2014 ). Other outgoing interactions from AXL that might warrant further investigation were TL6 to glucocorticoid-induced TNF receptor and NGF to nerve growth factor receptor, which has both been the target of interest in melanoma and other cancer fields ( Estrela et al , 2019 ; Kasemeier-Kulesa et al , 2018 ; Ramirez-Montagut et al , 2006 ; Zhu et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…CD271/p75-positive human metastatic melanoma cells may be reprogrammed to a benign cell type with ectopic NGF (Fig. 1C; Kasemeier-Kulesa et al, 2018). This is consistent with the above studies (Radke et al, 2017; Restivo et al, 2017) since we speculate that CD271-high expressing C8161 metastatic melanoma cells with low MART-1, MITF, and TYR expression may be preferentially responsive to NGF treatment and the induction of downstream signals leading to a melanocyte-like cell type.…”
Section: Discussionmentioning
confidence: 99%
“…We methodically determined the age, tissue type and ultimately NGF as the signal driving re-expression of MART-1, using a lentiviral MART-1:GFP reporter to observe dynamic changes in gene expression in co-cultures of human C8161 metastatic melanoma cells with various chick embryonic neural crest microenvironment tissues (Kasemeier-Kulesa et al, 2018). Our results showed that NGF receptors Trk-A and CD271 cooperate to induce MART-1 re-expression.…”
Section: Perspectivementioning
confidence: 99%